2020
DOI: 10.1016/j.stemcr.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

MiR-126 Regulates Properties of SOX9+ Liver Progenitor Cells during Liver Repair by Targeting Hoxb6

Abstract: Summary Liver progenitor cells (LPCs) have a remarkable contribution to the hepatocytes and ductal cells when normal hepatocyte proliferation is severely impaired. As a biomarker for LPCs, Sry-box 9 ( Sox9 ) plays critical roles in liver homeostasis and repair in response to injury. However, the regulation mechanism of Sox9 in liver physiological and pathological state remains unknown. In this study, we found that miR-126 positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Metabolic switch was reported to have a significant effect on Sox9 + hair follicle stem cell ( Kim et al., 2020 ). Our data have shown that Sox9 + hepatocytes properties are regulated by microRNAs during liver repair ( Yan et al., 2020 ). Here, our results illustrated that metabolic nuclear receptor, PPARα and FXR, played critical roles in regulating Sox9 + hepatocyte dynamic fate during both physiological (maintenance) and pathological (repair) regeneration processes.…”
Section: Discussionmentioning
confidence: 81%
“…Metabolic switch was reported to have a significant effect on Sox9 + hair follicle stem cell ( Kim et al., 2020 ). Our data have shown that Sox9 + hepatocytes properties are regulated by microRNAs during liver repair ( Yan et al., 2020 ). Here, our results illustrated that metabolic nuclear receptor, PPARα and FXR, played critical roles in regulating Sox9 + hepatocyte dynamic fate during both physiological (maintenance) and pathological (repair) regeneration processes.…”
Section: Discussionmentioning
confidence: 81%
“…After overexpression of miR-126, the acute lung injury in septic rats was improved, and the infiltration of inflammatory cells in lung tissue decreased accordingly. Studies on liver dysfunction in sepsis have found that miR-126 has a positive regulatory effect in the proliferation and differentiation of hepatocytes by inhibiting the expression of SRY box 9, suggesting that miR-126 has a potential role as a drug target for nucleic acid therapy of liver failure [ 33 ]. One study has demonstrated that regulating the miR-126 in sepsis can increase plasma IL-10, inhibit pulmonary vascular leakage, reduce liver and kidney injury, and improve the survival rate of mice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOX9 is a highly conserved member of the transcription factor family involved in the formation of cartilage and heart valves in mammals [ 22 , 23 ], contributing to the development of the pancreas, testes, liver, and other organs [ 24 28 ] and resulting in tumor proliferation, invasion, metastasis, and progression [ 6 8 ]. The report has confirmed that SOX9 is involved in collagen synthesis during heart development [ 23 ].…”
Section: Discussionmentioning
confidence: 99%